Sustainable housing materials in Shiraz - Samavati, Narges (2012)
Sustainable, or "green building," design and construction provide an opportunity to use resources more efficiently, while creating healthier and more energy-efficient homes. Successful green buildings leave a lighter footprint on the environment through conservation of resources, while at the same time balancing energy-efficient, cost-effective, low-maintenance products for construction needs. A similar concept of green building is natural building, which is usually on a smaller scale and tends to focus on the use of natural materials that are available locally In this thesis, sustainable housing materials for Shiraz houses are identified. In the first step the concept of sustainable materials are revealed and then, the characteristics of sustainable hosing materials are explained based on previous works and researches. Forward these works, same thesis for sustainable building materials in Sri Lanka is modified and its methodology is analyzed. Total characteristics and modifications of Shiraz and Shiraz houses are explained in next step, and then the analysis based on the sustainable material characteristics is started. Each objective is analyzed based on each house condition and the results are determined. The results show that, gathering the following materials would lead us to have a sustainable house in Shiraz: insulated cement block due to its low embodied energy and carbon emission for using in inside walls, the low amount of carbon emission and embodied energy of travertine stone in faced walls, steep clay roof as roofing system because it has the least carbon emission, and UPVC window for windows materials. In case of widows materials iron windows has the least amount of embodied amount of carbon emission and embodied energy but because they do not have many characteristics of sustainability, UPVC windows are preferred instead of these windows.